EFFECTIVENESS OF BOTANICAL INSECTICIDE FORMULATIONS AGAINST COCOA POD BORER CONOPOMORPHA CRAMERELLA (SNELL.) - Santiaji Bande, La Ode; HS, Gusnawaty; Mariadi, Mariadi; Nuriadi, Nuriadi (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Effectiveness of botanical insecticide formulations against cocoa pod borer Conopomorpha cramerella (Snell.). Cocoa pod borer (CPB), Conopomorpha cramerella (Lepidoptera: Gracillariidae), is a major pest on cocoa plants. The research aimed atfinding out botanical insecticide formulations that are effective against CPB. Plant materials used for preparing the formulations were cashew nut shell (Anacardium occidentale), whiteflower albizia (Albizia saponari), siam weed (Chromolaena odorata), and candle bush (Senna alata) extract. This research was conducted in the field using a randomized complete block design with the following treatments: formulation of cashew nut shell extract, cashew nut shell extract + whiteflower albizia bark extract, cashew nut shell extract + siam weed leaf extract, cashew nut shell extract + candle bush leaf extract, cashew nut shell extract + whiteflower albizia bark extract + siam weed leaf extract + candle bush leaf extract, and a synthetic insecticide formulation containing a mixture of lambda-cyhalotrin 106 g/L and thiametoxam 141 g/L as well as control (without botanical and synthetic insecticide treatment). The concentration of botanical pesticides applied from cashew nut shell extract used was 2.5 mL/L, while from other ingredients 250 mL/L.Variables observed were intensity of CPB infestation, degree of damage to the cocoa seed, and the efficacy of botanical insecticide treatments. The results showed that the test botanical insecticide formulations reduced the intensity of CPB infestation by 48.9?55.3% and the degree of seed damage by 52.3?58.2% compared with control. The efficacy of the test botanical insecticide formulations in controlling CPB was relatively the same when compared to each other, with a range of efficacy of 64.2?71.0%, but was lower than that of the synthetic insecticide formulation (92.8% efficacy). The implication of this research is that botanical insecticide formulations have the prospect of being continuously developed and have the potential to reduce the used of synthetic insecticides.